2017
DOI: 10.1016/j.addr.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

In vivo reprogramming of immune cells: Technologies for induction of antigen-specific tolerance

Abstract: Technologies that induce antigen-specific immune tolerance by mimicking naturally occurring mechanisms have the potential to revolutionize the treatment of many immune-mediated pathologies such as autoimmunity, allograft rejection, and allergy. The immune system intrinsically has central and peripheral tolerance pathways for eliminating or modulating antigen-specific responses, which are being exploited through emerging technologies. Antigen-specific tolerogenic responses have been achieved through the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 162 publications
(204 reference statements)
2
100
0
1
Order By: Relevance
“…This promotes the development of autoimmunity, drawing attention to the clinical importance of newly elaborated methods that enable the preservation or restoration of immune regulatory cell activity. Some of the currently investigated approaches are based on the observation that antigen coupled to autologous cells induces tolerance rather than effector responses . Accordingly, autologous erythrocytes were proposed to constitute good carriers of antigens to induce specific Treg cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This promotes the development of autoimmunity, drawing attention to the clinical importance of newly elaborated methods that enable the preservation or restoration of immune regulatory cell activity. Some of the currently investigated approaches are based on the observation that antigen coupled to autologous cells induces tolerance rather than effector responses . Accordingly, autologous erythrocytes were proposed to constitute good carriers of antigens to induce specific Treg cells …”
Section: Introductionmentioning
confidence: 99%
“…Some of the currently investigated approaches are based on the observation that antigen coupled to autologous cells induces tolerance rather than effector responses. 4 Accordingly, autologous erythrocytes were proposed to constitute good carriers of antigens to induce specific Treg cells. 5 Along these lines, recent findings revealed that intravenous administration of a high dose of syngeneic mouse red blood cells (sMRBC) coupled with hapten or protein antigen induces CD8 + suppressor T (Ts) cells in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Model systems of tolerance are being used to generate insights that can then be applied to different diseases [74]. In one example, PLGA NPs were used for intravenous and subcutaneous delivery of rapamycin to induce tolerance against coadministered model antigens [75].…”
Section: Biomaterials Improve Targeting Selectivity and Potency Of mentioning
confidence: 99%
“…As innate immunity members, APCs are responsible not only as an initial nonspecific line of defense, but also to present the antigens derived from self or nonself sources. This capability has made them intriguing targets in autoimmunity and cancer . Here, we review the cross‐talk of some innate immunity cells, and possible inspirations for designing biohybrid NPs.…”
Section: Negotiators With Biological Barriersmentioning
confidence: 99%